Intellectual Capital as a Core Competency for Competitive Advantage: A Case Study- - Nazem M.M. Malkawi; Kalid Al Omari; AzmiHalasa (Journal of Digital Information Management, 2018)
This paper aimed to study intellectual capital as a core competency for competitive advantage at pharmaceutical companies in Jordan. To complete the study, a case study was instituted by analyzing the responses of the pharmaceutical companies; the data collected were analyzed with a statistical package. The study concluded some results, the most appearing were; pharmaceutical companies depend on intellectual capital at a high level, competitive advantage also high, and there is a significant statistical effect of intellectual capital on competitive advantage as a whole and on all its indicators (leadership, human recourse, innovation, processes, and financial excellence) at (α ≤ 0.00). Researchers recommend pharmaceutical companies management and staff to reinforce using intellectual capital at all levels and functions and use it as a main source for competitive advantage in all its areas.